2013
DOI: 10.4103/0970-2113.106119
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cognitive functions in non-hypoxemic chronic obstructive pulmonary disease (COPD) patients and age-matched healthy volunteers using mini-mental state examination questionnaire and event-related potential, P300 analysis

Abstract: Objective:To assess sub-clinical cognitive dysfunctions in stable chronic obstructive pulmonary disease (COPD) patients having no hypoxemia vs. age-matched healthy volunteers using (i) an electrophysiological test: Auditory event related potential, P300 test and (ii) a questionnaire tool: Mini-mental state examination (MMSE) questionnaire.Materials and Methods:Eighty male subjects were included: 40 stable COPD patients (smoking history >20 pack years) and 40 healthy volunteers (HVs). Age, duration of illness, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
2
13
0
1
Order By: Relevance
“…3 However, several studies have provided evidence of cerebral dysfunction in nonhypoxemic COPD patients, indicating that hypoxemia per se is not the main factor. [4][5][6] This observation is unsurprising because an adequate oxygen supply to the brain is permanently ensured through cerebrovascular oxygen (O2) reactivity. During hypoxemia or oxygen desaturation, cerebrovascular O2 reactivity prevents cerebral hypoxia by increasing cerebral blood flow (CBF) up to 200%.…”
Section: Introductionmentioning
confidence: 99%
“…3 However, several studies have provided evidence of cerebral dysfunction in nonhypoxemic COPD patients, indicating that hypoxemia per se is not the main factor. [4][5][6] This observation is unsurprising because an adequate oxygen supply to the brain is permanently ensured through cerebrovascular oxygen (O2) reactivity. During hypoxemia or oxygen desaturation, cerebrovascular O2 reactivity prevents cerebral hypoxia by increasing cerebral blood flow (CBF) up to 200%.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Selokar et al [ 14 ] and Lam et al [ 15 ], with 10.3% and 11.8% of students having tried cigarette smoking, respectively. In contrast, Alrsheedi et al [ 16 ], Sreeramareddy et al [ 17 ] and Surani et al [ 18 ] reported that 23%, 31.7% and 40% of students tried smoking, respectively. In the present study, among male medical students, one-fourth had ever smoked cigarettes compared with 1.8% among female medical students.…”
Section: Discussionmentioning
confidence: 97%
“…Son dönemde yapılan bir çalışmada hipoksemisi olmayan KOAH hastalarında da kognitif fonksiyonlarda bozulma olduğu gösterilmiştir (17). Ayrıca yaşlı KOAH'lı olgularda kognitif fonksiyonların yaşla ilişkili olarak kan akımında azalma, eğitim durumu, hastalıkla ilişkili olarak arteryel oksijen içeriğinde azalma ve hem hastalık hem de yaş ile ilişkili olarak fiziksel aktivitede azalmayla etkilenebileceği belirtilmiştir (18)(19)(20) hasta grubumuzun da hipoksisi olmayan 50 yaş ve üs-tü hastalardan oluştuğu göz önüne alınırsa kognitif fonksiyonlardaki bu azalmada yaş ve KOAH nedeniyle ortaya çıkan sistemik inflamasyon, oksidatif hasar ve fiziksel aktivitedeki kısıtlanmanın rolü olduğu düşünü-lebilir.…”
Section: Discussionunclassified